Magnesium and Vascular Changes in Hypertension - Ana Rosa Cunha; Bianca Umbelino; Margarida L. Correia; Mario Fritsch Neves (International Journal of Hypertension)
Many factors have been implicated in the pathogenesis of hypertension, including changes in intracellular concentrations of calcium, sodium, potassium, and magnesium. There is a significant inverse correlation between serum magnesium and incidence of cardiovascular diseases. Magnesium is a mineral with important functions in the body such as antiarrhythmic effect, actions in vascular tone, contractility, glucose metabolism, and insulin homeostasis. In addition, lower concentrations of magnesium are associated with oxidative stress, proinflammatory state, endothelial dysfunction, platelet aggregation, insulin resistance, and hyperglycemia. The conflicting results of studies evaluating the effects of magnesium supplements on blood pressure and other cardiovascular outcomes indicate that the action of magnesium in the vascular system is present but not yet established. Therefore, this mineral supplementation is not indicated as part of antihypertensive treatment, and further studies are needed to better clarify the role of magnesium in the prevention and treatment of cardiovascular diseases.